Development of Learning Media for Introductory Information and Communication Technology Courses - Mustapa, Mahmud; Ummiati Rahmah; Muh. Asjart (Ceddi Journal of Education, 2022)
This research aims to (1) assess the current learning conditions in the "Introduction to Technology of Information and Communication" course within the Electrical Engineering Education Department at Makassar State University; (2) outline the developmental stages of web-based learning media tailored for this course; and (3) evaluate the validity of the developed learning media based on assessments from material and media experts. The study employs the ADDIE development model, focusing on the phases of Analysis, Design, and Development. Conducted at the Electrical Engineering Education Department at Makassar State University, the research involved material and media experts as informants, with data gathered through observations and questionnaires and analyzed using descriptive techniques. The findings reveal the structured developmental process of the web-based learning media, which encompasses the Analysis, Design, and Development phases. The validation results show that the material experts rated the media's feasibility at 82.81%, while design experts gave it a rating of 89.58%, indicating a high level of effectiveness. The use of the Research and Development (R&D) approach in this study has proven successful in creating a robust educational tool that can significantly enhance the learning experience in the course. This research contributes to the broader field of educational technology by demonstrating the effectiveness of web-based learning media, particularly in technical education. Its implications extend to improving student engagement, fostering interactive learning, and providing scalable educational solutions in higher education, thereby advancing the quality of education in the digital age.